Morphological, molecular and pathological variability of Phytophthora spp. from perennial crops in Malaysia - Musanif, Latifah (2016)
Phytophthora causes various types of devastating diseases in different types of plants including annual and perennial crops, ornamental and forest trees in the tropical, subtropical, and temperate climates. In the tropics, Phytophthora spp. is considered as one of the most destructive pathogens of cocoa, rubber, durian and other commodity crops. However, the potential of Phytophthora spp. to cross-infect susceptible non-host plants were not extensively studied. Phytophthora spp. cross-infection studies are particularly important in intercropping systems practiced in plantations. Hence, the purpose of this study was to isolate, characterize and identify Phytophthora spp. from major perennial crops in Malaysia. In addition, pathogenicity and cross-pathogenicity of Phytophthora spp. between hosts and non-hosts such as oil palm were also studied. Identification of Phytophthora spp. was done through morphological, cultural and molecular characterizations based on Internal Transcribed Spacer (ITS) regions of ribosomal deoxyribonucleic acid (rDNA). Pathogenicity tests were carried out to confirm its pathogenicity towards its native host. Cross-pathogenicity tests were conducted to determine the potential of Phytophthora spp. in infecting susceptible non-hosts. Morphological characterizations of the isolated Phytophthora spp. indicated that most isolates from cocoa and durian formed striate and stellate colonies while isolates from rubber exhibited fluffy colonies on cornmeal agar (CMA), carrot agar and vegetable juice agar (V8). Optimum mycelial growth for all isolates was 28 ± 1.5°C. In addition, sporangia from cocoa and durian were caducous with length to breadth ratios ranging from 1.51 to 1.69 and possessed short occluded pedicels. However, Phytophthora isolates from rubber displayed non-caducous sporangia with length to breadth ratios of 1.3 to 1.38. Nonetheless, all isolates were observed to produce abundant chlamydospores after two weeks of incubation. Therefore, in the present study, 18 isolates of Phytophthora spp. were successfully isolated from cocoa, durian and rubber; 12 isolates from cocoa and durian were identified as P. palmivora, while six isolates were from rubber, Phytophthora nicotianae (synonym P. parasitica). Molecular identifications supported morphological and cultural characterizations of the isolated Phytophthora spp. In-vitro pathogenicity tests of 18 isolates on detached leaves and unripe cocoa pods exhibited the progressive development of lesions on its native host. Moreover, lesions were also developed in all wounded detached leaves and unripe cocoa pods regardless of hosts and isolates in cross-pathogenicity tests. However, there was a significant difference in the length of lesions developed, whereby longer lesions were detected on its native host compared to its non-native host. Additionally, inoculation of Phytophthora isolated from durian stem canker, cocoa pod rot, and rubber pod rot displayed infections on young immature oil palm leaflets by the development of discoloration. This discoloration developed after three days of incubation under moist conditions. Cross-inoculation studies also demonstrated that Phytophthora spp. was pathogenic to oil palm seedlings through the development of lesions on the buds. The pathogens were successfully re-isolated from the developed lesions of inoculated tissues, thus fulfilling Koch’s postulates and this confirmed that Phytophthora spp. are pathogenic to oil palm. As conclusion, both conventional method (morphology and cultural studies), together with molecular identification confirmed that Phytophthora isolates from cocoa and durian were P. palmivora, whilst rubber isolates known as P. nicotianae. There was development of lesion on plant tissues regardless of host and non-host was noted, however more aggressiveness and length of lesion on own host in in-vitro test was observed. Both of in-vitro test and field trials also showed that P. palmivora and P. nicotianae in the present study were pathogenic to immature oil palm leaflets.